Economic analysis of commercial seed yam production systems in the Subhumid ecologies of the river Niger - Ibana, S.; Coyne, Danny L.; Claudius-Cole, A.O.; McNamara, N.; Morse, S. (Informa UK Limited, 2012)
Published studies to date have suggested that seed-yam (Dioscorea rotundata) production in Nigeria using minisett (∼0.025 kg) technology or an adapted form of the technology using larger setts (0.08 to 0.1 kg) was not profitable. But these studies were often conducted under artificial conditions where labor inputs may have been inflated. This paper describes the results of a questionnaire-based survey designed to explore the economic performance of seed-yam producers in the Ilushi hinterland area of Nigeria, along the western bank of the River Niger. It is the first economic study of this important source of seed yam. Farmers in this area specialize in seed-yam production via two techniques: the use of small whole tubers (0.05 to 0.1 kg) and setts (cut pieces of tuber) of 0.12 to 0.15 kg. Results suggest that seed-yam production is profitable in the area using both systems, with gross margins (revenue – costs) of between Naira 23,395 and 61,375/ha (or US$175 to $458/ha).